2016
DOI: 10.1016/j.cub.2016.07.008
|View full text |Cite|
|
Sign up to set email alerts
|

Muscle- and Skin-Derived Cues Jointly Orchestrate Patterning of Somatosensory Dendrites

Abstract: Summary Sensory dendrite arbors are patterned through cell-autonomously and non-autonomously functioning factors [1–3]. Yet, only a few non-autonomously acting proteins have been identified, including semaphorins [4, 5], brain derived neurotrophic factors (BDNF) [6], UNC-6/Netrin [7], and the conserved MNR-1/Menorin–SAX-7/L1CAM cell adhesion complex [8, 9]. This complex acts from the skin to pattern the stereotypic dendritic arbors of PVD and FLP somatosensory neurons in Caenorhabditis elegans through the dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 44 publications
4
65
0
Order By: Relevance
“…Finally, the muscle-secreted protein LECT-2 interacts with the DMA-1 complex to promote PVD branching (11,18). Consistent with this, we found that loss of lect-2 causes defects in dauer-specific IL2 branching that can be rescued through muscle-specific expression ( Fig.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Finally, the muscle-secreted protein LECT-2 interacts with the DMA-1 complex to promote PVD branching (11,18). Consistent with this, we found that loss of lect-2 causes defects in dauer-specific IL2 branching that can be rescued through muscle-specific expression ( Fig.…”
Section: Resultssupporting
confidence: 83%
“…However, we show that the DMA-1 complex is not sufficient to induce branching in the IL2s. Overexpression of DMA-1 in the IL2s during non-dauer stages did not induce branching despite the presence of SAX-7, MNR-1, and LECT-2 (9,18). Similarly, we found that during dauer the FLPs stop branching despite its expression of DMA-1.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The LRR (Leucine Rich Repeat) protein DMA-1 likely acts in the same pathway as it shows a similar mutant PVD branching defect (Dong et al, 2013; Smith et al, 2013). DMA-1 mediates dendritic outgrowth as a PVD-expressed component of a quarternary complex containing the cell surface proteins SAX-7/L1CAM and Menorin/MNR-1 in the epidermis and the soluble factor LECT-2 (Díaz-Balzac et al, 2016; Dong et al, 2013; Liang et al, 2015; O’Brien et al, 2016; Salzberg et al, 2013; Zou et al, 2016). These interactions are necessary for 3° and 4° branching, but additional epidermal cues are likely required for pioneer 2° branch outgrowth as the dma-1 mutant phenotype is more severe than that of either sax-7 , mnr-1 , or lect-2 .…”
Section: Discussionmentioning
confidence: 99%
“…While C. elegans has been used extensively as a model for axon development [11], considerably less attention has been paid to its dendrites. Most of the work has focused on interesting sensory neurons with complex branched dendrites, and has revealed mechanisms of dendritic branch formation and spacing [12][13][14][15][16][17][18][19][20][21][22][23], dendritic self-avoidance [24], and even dendrite tiling [25]. By comparison, dendrites with simple unbranched morphologies have been used as a model for understanding axon-dendrite polarity [26,27].…”
Section: Introductionmentioning
confidence: 99%